PEMBELAJARAN INTERDISIPLINER: EDUKASI HOLISTIK UNTUK MENINGKATKAN LITERASI SAINS DAN LITERASI BACA ANAK SD DI DESA BINJAI - Tariza Fairuz; Larasati Arum Utami; Vera Marisa (LPPI UMN AL WASHLIYAH, 2025)
Science literacy and reading literacy are two key competencies that not only support academic success but also prepare children to face global challenges in the 21st century. Science literacy includes the ability to understand scientific concepts, think critically, and apply that knowledge in everyday life. Meanwhile, reading literacy involves the ability to understand, analyze, and use information from written texts. Science literacy and reading literacy of elementary school children in Binjai Village are still low and need holistic education with interdisciplinary learning programs. This community service program aims to improve science literacy and reading literacy of elementary school children in Binjai Village through interdisciplinary learning. The implementation method in this community service activity is in accordance with the partner's problem, through training in interdisciplinary learning that includes aspects of science literacy and reading literacy in English and Arabic adapted from quantitative research methods with a one-class pretest-posttest design. This service was carried out in Binjai Village, Tebing Syahbandar District, Serdang Bedagai Regency. There were 30 elementary school children who participated in this activity. The results of this activity show an increase in science literacy and reading literacy of elementary school children in Binjai village.